1990
DOI: 10.1021/bi00462a016
|View full text |Cite
|
Sign up to set email alerts
|

Structural comparison of anticancer drug-DNA complexes: adriamycin and daunomycin

Abstract: The anticancer drugs adriamycin and daunomycin have each been crystallized with the DNA sequence d(CGATCG) and the three-dimensional structures of the complexes solved at 1.7- and 1.5-A resolution, respectively. These antitumor drugs have significantly different clinical properties, yet they differ chemically by only the additional hydroxyl at C14 of adriamycin. In these complexes the chromophore is intercalated at the CpG steps at either end of the DNA helix with the amino sugar extended into the minor groove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
424
0
2

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 560 publications
(461 citation statements)
references
References 31 publications
35
424
0
2
Order By: Relevance
“…the helical rise at the central TpA step is much greater (0.42 nm) and the roll angle is increased to 12'. The distortions at the central base pairs in the d(CGTACG) -daunomycin complex and the even greater distortions at the TpA step in the d(TGTACA) -4'-epiadriamycin complex are coincident with changes in the drug conformation relative to that of complexes of anthracycline antibiotics with the d(CGATCG) complexed with daunomycin (Wang et al, 1987) and d(CGTACG) coniplexed with adriamycin and daunomycin (Frederick et al, 1990).…”
Section: Results and Dlscusslonmentioning
confidence: 95%
See 1 more Smart Citation
“…the helical rise at the central TpA step is much greater (0.42 nm) and the roll angle is increased to 12'. The distortions at the central base pairs in the d(CGTACG) -daunomycin complex and the even greater distortions at the TpA step in the d(TGTACA) -4'-epiadriamycin complex are coincident with changes in the drug conformation relative to that of complexes of anthracycline antibiotics with the d(CGATCG) complexed with daunomycin (Wang et al, 1987) and d(CGTACG) coniplexed with adriamycin and daunomycin (Frederick et al, 1990).…”
Section: Results and Dlscusslonmentioning
confidence: 95%
“…r.m.s., root mean square. have characteriscd the molecular intcractions between these molecules and a number of oligonucleotides (Wang et al, 1987, Moore et al, 1989, Frederick et al, 1990. These studies have shown that the aglycone moiety intercalates at a pyriniidine-purine step, d(CpG) and the amino sugar binds in the minor groove of the B-DNA duplex.…”
mentioning
confidence: 99%
“…To measure the time resolved gene responses to Roc-A, RNA was isolated from Roc-A-treated (50 nM) normal T and Jurkat T cells at t 5 [0, 1,2,3,4,6,8,10,14,20,28,36] and t 5 [0. 5,1,2,3,4,5,6,7,8,10,12,14,16,20,24,28,32,36] hr, respectively. The quality of total RNA was controlled with an Agilent 2100 Bioanalyzer (Agilent Technologies GmbH, Berlin, Germany).…”
Section: Rna Preparation and Dna Microarray Analysismentioning
confidence: 99%
“…23 To investigate whether Roc-A acts as an intercalator, we compared the action of Roc-A to that of the DNA intercalation anticancer drug doxorubicin (trade name Adriamycin). 24 When DNA is damaged, DSBs trigger recruitment of ATM to the damage site which in turn phosphorylates histone H2AX (yielding gH2AX) leading to foci formation. 25,26 Therefore, we used gH2AX as a readout to investigate the status of gH2AX levels in living cells following Roc-A treatment.…”
Section: Roc-a Does Not Induce Massive Dna Damage As Compared To Dna mentioning
confidence: 99%
“…Reactive oxygen species (ROS) may also cause DNA damage. To investigate the mechanisms of tagalsins‐induced DNA damage, we compared tagalsins with doxorubicin (trade name adriamycin) which damages DNA by d(CGTACG) intercalation 20. Jurkat T cells were treated with TC, TF or doxorubicin in the absence or presence of the anti‐oxidant N ‐acetyl‐cysteine (NAC).…”
Section: Resultsmentioning
confidence: 99%